Using Immersive Virtual Reality to Improve Choosing by Advantages System for the Selection of Fall Protection Measures - Brioso, X.; Calderón-Hernandez, C.; Irizarry, J.; Paes, D. (American Society of Civil Engineers (ASCE), 2019)
The use of immersive virtual reality (IVR) with mobile platforms in the construction industry has been researched, but its application in the evaluation and selection of fall protection equipment presents a new challenge. On the other hand, the choosing by advantages (CBA) decision-making system has been applied with success in several construction projects and has proven to be beneficial over more traditional methods. In this study, a qualitative analysis is made to determine the impact of IVR in the selection of a fall protection system and in the increase of transparency when using the CBA method. The framework used consisted of performing two experiments with CBA for participants to choose the best option between a safety net and a lifeline during the construction of a concrete structure building. On the first experiment, the alternatives were shown in videos and in the second experiment the VR platform was used. In both cases, the same option was selected. Finally, a survey was conducted, and the findings indicate that IVR improves the process of reaching agreement through collaborative planning, helps to better comprehend the relationship between the safety system and the production system and enriches the CBA method by giving stakeholders a more comprehensive approach.
Keywords: Transparency (behavior); Virtual reality; Process (computing); Computer science; Selection (genetic algorithm); Simulation; Engineering; Human–computer interaction; Computer security; Artificial intelligence; https://purl.org/pe-repo/ocde/ford#1.02.00